2011 14th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing 2011
DOI: 10.1109/isorc.2011.34
|View full text |Cite
|
Sign up to set email alerts
|

Design Space Exploration of Object Caches with Cross-Profiling

Abstract: Abstract-To avoid data cache trashing between heapallocated data and other data areas, a distinct object cache has been proposed for embedded real-time Java processors. This object cache uses high associativity in order to statically track different object pointers for worst-case execution-time analysis. However, before implementing such an object cache, an empirical analysis of different organization forms is needed. We use a cross-profiling technique based on aspect-oriented programming in order to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The results are in line with the evaluation of the object cache based on static WCET analysis [3] and cache simulation based on cross-profiling [9]. The improvement scales to some extent with larger object caches.…”
Section: B Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results are in line with the evaluation of the object cache based on static WCET analysis [3] and cache simulation based on cross-profiling [9]. The improvement scales to some extent with larger object caches.…”
Section: B Discussionsupporting
confidence: 78%
“…To verify the design decisions we have also evaluated the proposed object cache by executing large Java benchmarks (DaCapo) with cross-profiling [9]. With a simulation of the object cache we where able to compare the high-associative organization with a standard cache organization.…”
Section: Wcet Analysismentioning
confidence: 99%
“…Simulations with larger workloads (DaCapo benchmarks) show a hit rate of 70% to 90% for small heap caches [39]. In this paper it is also shown that most hits stem from temporal locality and not spatial locality.…”
Section: Cache Analysismentioning
confidence: 65%